The new generation of "Ruang Sehati” portable lactation pod as a part of wellness tourism in Yogyakarta City: A design thinking method - Okinarum, Giyawati Yulilania (Journal of Health Technology Assessment in Midwifery, 2024)
Public lactation rooms in popular tourist destinations continue to fall short of the Indonesian government's basic guidelines. Thus, we developed the first portable lactation pod in Indonesia, focusing on user demands. This study employed the design thinking method, combined with qualitative research and quality improvement techniques that focus on user needs. Thirty participants were interviewed on different days, Saturday and Sunday, in the first week of July, with each interview lasting 30 minutes. The interview was only conducted at the "empathize" and "testing" stages. From July to September 2023, the stages of "empathize," "define," "ideate," "prototype," and “test” were completed. Four themes were found during the development process of the newest generation of the portable lactation pod, "Ruang Sehati.” These themes are the essential elements lactating mothers and their babies need at the portable lactation pods in tourist destinations: functional, natural, aesthetic, and educational elements. The harmonization of architectural art, tourism, and health would enable us to bring this innovation to build a national pilot initiative that promotes wellness tourism in Yogyakarta.